Una aproximación histórica a los negocios internacionales y a la presencia extranjera en la Antioquia del siglo XIX (2019)
It is in the Antioquia’s economic development, since the independence until the XIX century, where the first outlines of the regional internationalization process can be traced. A variety of associations and industrial innovations, representatives to the process were derived from the foreign presence in the region during that period. A process in which the mining activity, its insertion into the international trade, and the benefits obtained make possible that the region keep a manufactured product import capacity, which had not a big size, but had an important stability and a relative permanence. Thus, mining and trade were the excellent opening binomial, once the colonial regime was over.